Act of 1880 for Counteracting Lottery in Italy (Quarterly Journal of Economics, 1887)
Act of 1880 for Counteracting Lottery in Italy Get access The Quarterly Journal of Economics, Volume 1, Issue 2, January 1887, Pages 226–227, https://doi.org/10.1093/qje/1.2.226 Published: 01 January 1887